Analisis Nilai-Nilai Pendidikan Islam dalam Buku Pribadi Hebat Karya Buya Hamka - M. Hafizh Abdulloh; Moh. Sakir; Vava Imam Agus Faisal (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to analyze the values ​​of Islamic education contained in the book Pribadi Hebat by Buya Hamka. A qualitative approach is used in this study, with a content analysis method on data in the form of reflective and argumentative narratives that are relevant to the book. The results of the analysis show that this book contains various values ​​of Islamic education which are divided into three categories. First, the values ​​of faith education, in the book Pribadi Hebat by Buya Hamka, several values ​​of faith education are found, namely the teachings of faith as the foundation of the person and piety as the perfection of faith. Second, the values ​​of worship education, the values ​​of worship education in the book Pribadi Hebat are divided into 2, namely mahdah worship and ghairumahdah worship. The values ​​of mahdah worship education in the book Pribadi Hebat are the importance of maintaining cleanliness with ablution and prayer as the main source of personal strength, while the values ​​of ghairumahdah education in the book Pribadi Hebat are teachings about all work that is based on the intention of seeking Allah's pleasure is worship. The three values ​​of moral education, in the book Pribadi Hebat by Buya Hamka, several values ​​of moral education are found, including the importance of morals, empathy, courage, admitting one's shortcomings, self-confidence, reprehensible attitudes, willingness, responsibility, and patience as personal capital that will never run out.